Coupling coordination of agricultural water-economy systems in China: evidence from high-stress hydrological zones in a major grain-producing province - Yang, Yang; Chen, Junmin; Li, Zhaoguang; Wang, Jinxing; Zhou, Xinyue (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis study aligns with the United Nations Sustainable Development Goals (SDGs), examining the critical trade-offs between agricultural water use and agricultural economic growth in Henan Province, China’s major grain-producing region (SDG 2: Zero Hunger; SDG 6: Clean Water and Sanitation).MethodsBased on 19 years of municipal-level panel data from Henan Province, this study employs methods such as the coupling coordination degree model and Moran’s I index to assess agricultural economic development and agricultural water resources utilization, and to explore their directions for synergistic development.ResultsThe results indicate that, although the overall trends in agricultural economic development and agricultural water resource utilization have improved, the momentum for further agricultural economic growth is weak, and the subsystems of agricultural water resources show contradictory changes. Consequently, despite some improvements, the coupling coordination level between the two remains relatively low and unstable. Spatially, the improvement in coordination levels shows a south > central > north trend, leading to a shift in the coordination pattern from southeast > northwest to south > central > north. Regions with low coordination levels are concentrated in the north, while those with high coordination levels are mainly in the south.DiscussionTo facilitate the smooth implementation of the United Nations Development Goals in China, it is imperative to establish measures such as a spatiotemporal-based agricultural water resources-economy coordinated governance system.